Oh, dude, it's like asking me for the cool, alternative name for your boring math problem. So, 3a plus 5 is basically the same as saying "three times a, plus five." It's just a fancier way of dressing up your numbers, you know?
An equivalent expression to 3a plus 5 would be 5 plus 3a, as addition is commutative. This means the order of the terms can be switched without changing the result. Another equivalent expression could be 3a + 5, as the addition operation is associative, allowing us to group the terms in any order. Finally, we could also write the expression as 3(a) + 5 to show that the coefficient 3 applies to the variable a.
The expression 9+5 is equivalent.
If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1
3a + a = 4a Example: a = 5 (3x5) + 5 = 15 + 5 = 20 = 4 x 5
5*(2q + 5r)
-5
-2
The expression 9+5 is equivalent.
The expression 4a - 5 - a + 2 can be simplified by combining like terms. Combining the terms with 'a', we get 4a - a = 3a. Combining the constants, we get -5 + 2 = -3. Therefore, the simplified expression is 3a - 3.
The expression is 33.
6a-3
5 + n
5(y + 1)
If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1
It is equivalent to 15x+10
4a + 7
The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.
3a + a = 4a Example: a = 5 (3x5) + 5 = 15 + 5 = 20 = 4 x 5